Uji Efektivitas Antidepresan Mencit (Mus Musculus) Galur Swiss Menggunakan Ekstrak Etanol Kulit Jeruk Sunkist (Citrus sinensis (L.) Osbeck) - Nofita, Nofita; Safitri, Erika Indah; Febriasti, Nisa A (Jurnal Ilmiah Wahana Pendidikan, 2024)
Depression is a disorder of a person's emotional or mental state which is characterized by persistent feelings of anxiety, sadness. Orange peel contains flavonoids, tannins, polyphenols and triterpenoids which are quite effective as antidepressants by providing a relaxing function to the body. This study aims to determine the antidepressant effectiveness of ethanol extract of sunkist orange peel (Citrus sinensis (L.) Osbeck). The method used for antidepressant test is FST (Forced Swim Test) and TST (Tail Suspension Test) and observed immobility time before and after treatment. The antidepressant test used 20 mice divided into 5 treatments, namely negative control (Na-CMC 0.5%), positive control (Amitriptyline 25 mg), doses of sunkist orange peel extract 200 mg/kgBW, 300 mg/kgBW and 400 mg/kgBW given orally. Immobility time data before and after treatment were statistically analyzed with Paired T-Test. The test results stated that all doses of ethanol extract of sunkist orange peel showed antidepressant effectiveness in mice that differed not statistically significant (p>0.05).